Критерії ефективності висококонкурентної продукції - Овсієнко, Артур Ігорович; Овсієнко, Катерина Юріївна (Видавничий дім "Інтернаука", 2020)
У статті наведено підходи до трактування поняття "конкурентоспроможна продукція". Обґрунтовано сутність висококонкурентної продукції. Визначено місце цінності в процесі створення нової продукції. Проаналізовано підходи зарубіжних науковців щодо створення цінності висококонкурентної продукції. На основі аналізу специфіки виражених та прихованих потреб споживачів, а також їх зміну в часі, встановлено, що одним із критеріїв ефективності висококонкурентної продукції є надання вищої споживчої цінності. Обґрунтовано, що ефективність висококонкурентної продукції залежить від можливості вирішення прихованих та майбутніх потреб споживачів. Виявлено місце провідних користувачів в процесі ідентифікації прихованих потреб ринку. Зазначено роль дизайн-мислення в процесі створення висококонкурентної продукції. Визначено, що інтеграція технології та дизайну для створення нового значення висококонкурентної продукції належить до критеріїв ефективності.

In today's dynamic environment innovations form new requirements for products, the implementation of which determines the possibility of achieving the desired results of economic activity. Creating highly competitive products involves knowledge-intensive production process. However, the use of an innovative approach to production should be carried out on the basis of purposefulness, i.e. to provide the effectiveness criteria achievement. The issue of achieving effectiveness in the production of highly competitive products is quite relevant for the modern realities of doing business, so it is quite actively covered in the scientific literature. Therefore, there is a need to systematize the scientific achievements of domestic and foreign scientists to identify the main criteria for the effectiveness of highly competitive products. The purpose of the article is to determine the main criteria that determine the effectiveness of highly competitive products. The article presents approaches to the interpretation of the "competitive product" concept. The essence of highly competitive products as a type of scienceintensive products that have sufficient competitive advantages to rival in the national and global market is substantiated. The place of value in the process of creating new products is determined. The approaches of foreign scientists to create the value of highly competitive products are analyzed. Based on the analysis of the specifics of the expressed and hidden needs of consumers, as well as their change over time, it is established that one of the criteria for the effectiveness of highly competitive products is to provide higher consumer value. It is substantiated that the effectiveness of highly competitive products depends on the ability to fulfill the hidden and future needs of consumers. The place of leading users in the process of identification the hidden needs of the market is revealed. The role of design thinking in the process of creating highly competitive products is indicated. It is determined that the integration of technology and design to create a new value of highly competitive products belongs to the criteria of effectiveness.
Criteria for the effectiveness of highly competitive products
Keywords: економічна діяльність; маркетингова діяльність; конкурентоспроможність; провідні користувачі; створення цінності продукції; продукція B2C; highly competitive products; efficiency of innovations; competitive products; efficiency criteria; leading users; B2C products; value creation of products